Pengaruh Persepsi Manfaat, Persepsi Kemudahan, Dan Persepsi Keamanan Terhadap Keputusan Penggunaan E-Wallet Pada Mahasiswa STIE Bank BPD Jateng - Yuliani Dwi Rahmawati; Rahmi Yuliana (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2020)
This study aims to determine the effect of perception of benefits, perception of ease, and security perception on the decision to use e-wallet for STIE Bank BPD Jateng students. The population in this study is the active students of 2016 - 2019 who are in STIE Bank BPD Jateng, amounting to 824 students. The sampling technique used in this study uses snowball sampling and The number of samples selected was 90. Data collection methods with questionnaires distributed online. The analytical tool in this study is multiple linear regression analysis. The results show that the perception of benefits, perceived convenience, and perceived security have a positive and significant effect on the decision to use e-wallet for students. Variable perception of security has a dominant influence on the decision to use e-wallet for students. Security is indeed the most important in the decision to use e-wallet because someone feels safe and protected.